The Effect of Language Learning Strategies on Proficiency, Attitudes and School Achievement - Habók, Anita; Magyar, Andrea (Frontiers in Psychology, 2018)
This study examines language learning strategy (LLS) use in connection with foreign language attitude, proficiency and general school achievement among lower secondary students in Years 5 and 8 (n=868) in Hungary. An adapted version of the Strategies Inventory for Language Learning questionnaire was used for data collection. The results showed that Hungarian students mainly engage in metacognitive strategies in both years. Differences between more and less proficient language learners’ strategy use have also been found. With regard to the effect of LLS on foreign language attitude, the foreign language mark and school achievement, path analysis indicated a good fit in both years. The metacognitive, social and memory strategies primarily influenced foreign language attitudes and marks in Year 5. The metacognitive strategies had a slight impact on school achievement as well as on foreign language marks. We demonstrated the dominant effect of metacognitive strategies and the low effect of memory strategies in Year 8. In addition, metacognitive strategies also influenced foreign language marks. The effect of foreign language marks on school achievement was also remarkable. There was a strong impact on the children’s attitudes through these variables.